Elaboración y uso de briquetas de cáscara de coco (cocos nucifera l) más papel reciclado como fuente energética en Iquitos 2022 - López García, Ericka Vanessa (2024)
The study was executed in the Project of species forager in the I am founded agronomic, with the objective of preparing briquettes with coconut shell more residual papers, the population was formed by 16 briquettes, the design was experimental and the method of type experimental evaluative was used, the DCA was used with four methods and four reiterations, being reached the conclusion: with respect to the longitude and final weight according to the order the T4 (26 cm and 86.25 g), T3 (24 cm and 82.50 g), the T2 (24 cm and 81 g) and the T1 with (21.75 cm and 77 g); with respect to the diameter the T4 (50% coconut shell more 50% of recycled paper) it presents a stocking of (5.05 cm), the T3 (40% of coconut shell more 60 paper%) with (4.98 cm), the T1 with (4.45 cm) and the T2 with (4.05 cm), the best time of ignition the T3 occupied it with (9.73 minutes), the second place has it the T1 with (10.68 minutes), then the T2 with (11.33 minutes) and the T4 in last place with (11.42 minutes); with respect to the time of boil of the water the T3 occupies the best place with (20 minutes), followed by the T1 with (24.22 minutes) in third position the T2 is located with (29.40 minutes) and the T4 is in last with (30.58 minutes). With concerning this it is accepted.